Myocardial tissue characterization in Chagas' heart disease by cardiovascular magnetic resonance. Issue 1 (December 2015) - Torreão, Jorge; Ianni, Barbara; Mady, Charles; Naia, Evandro; Rassi, Carlos; Nomura, Cesar; Parga, José; Avila, Luis; Ramires, José; Kalil-Filho, Roberto; Rochitte, Carlos
Abstract Background Chagas' heart disease is an important public health problem in South America. Several aspects of the pathogenesis are not fully understood, especially in its subclinical phases. On pathology Chagas' heart disease is characterized by chronic myocardial inflammation and extensive myocardial fibrosis. The latter has also been demonstrated by late gadolinium enhancement (LGE) by cardiovascular magnetic resonance (CMR). In three clinical phases of this disease, we sought to investigate the presence of LGE, myocardial increase in signal intensity in T2-weighted images (T2W) and in T1-weighted myocardial early gadolinium enhancement (MEGE), previously described CMR surrogates for myocardial fibrosis, myocardial edema and hyperemia, respectively. Methods Fifty-four patients were analyzed. Sixteen patients with the indeterminate phase (IND), seventeen patients with the cardiac phase with no left ventricular systolic dysfunction (CPND), and twenty-one patients with the cardiac phase with left ventricular systolic dysfunction (CPD). All patients underwent 1.5 T CMR scan including LGE, T2W and MEGE image sequences to evaluate myocardial abnormalities. Results Late gadolinium enhancement was present in 72.2 % of all patients, in 12.5 % of IND, 94.1 % of the CPND and 100 % of the CPD patients (p  < 0.0001). Myocardial increase in signal intensity in T2-weighted images (T2W) was present in 77.8 % of all patients, in 31.3 % of the IND, 94.1 % of the CPND and 100 % of the CPD patients (p  < 0.0001). T1-weighted myocardial early gadolinium enhancement (MEGE) was present in 73.8 % of all patients, in 25.0 % of the IND, 92.3 % of the CPND and 94.1 % of the CPD (p  < 0.0001). A good correlation between LGE and T2W was observed (r = 0.72, andp  < 0.001). Conclusions Increase in T2-weighted (T2W) myocardial signal intensity and T1-weighted myocardial early gadolinium enhancement (MEGE) can be detected by CMR in patients throughout all phases of Chagas' heart disease, including its subclinical presentation (IND). Moreover, those findings were parallel to myocardial fibrosis (LGE) in extent and location and also correlated with the degree of Chagas' heart disease clinical severity. These findings contribute to further the knowledge on pathophysiology of Chagas' heart disease, and might have therapeutic and prognostic usefulness in the future.